The influence of coaches` leadership styles on athletes` satisfaction and team cohesion: A meta-analytic approach - Kim, H. D.; Cruz, A. B. (International Journal of Sports Science & Coaching, 2016)
As a team leader, a coach plays a significant role in helping his/her players obtain high levels of performance and success; therefore, a coach should possess skills to help his/her athletes accomplish such daunting tasks. We conducted a meta-analysis to evaluate the relationship between coaching behaviors, athlete satisfaction, and team cohesion. Moreover, we examined gender as a possible moderating variable. Two-hundred eighty-eight effect sizes were obtained from 24 studies that used Chelladurai`s sports leadership scale. Overall, a moderate relationship was found between leadership and cohesion, and a large relationship was found between leadership and satisfaction. Training/instruction was the highest contributor for both relationships. Gender moderated both relationships. It is important to recognize the influence leadership behaviors have on the psychological state of players, especially as sports evolve to be more challenging and multifaceted. PREVIEW FROM AUTHOR